THE PROBABILISTIC METHODS FOR SOLVING CONTROL TASKS OF THE ROAD-BUILDING MACHINES PARK - Radkevych, O. V.; Yakovliev, S. O.; Kramar, I. Ye. (Science and Transport Progress, 2008)
The analysis of existing methods of management by the parks of building machines is conducted, it is marked that all of them have their advantages and demerits. Therefore in the real management system it is necessary to apply not someone of them but a few incorporated into the system.